Influence of sex on the "Athlete`s Heart" in trained cyclists - Rowland, T.; Roti, M. (Journal of Science and Medicine in Sport, 2010)
Compared to females, male endurance athletes have generally been considered to demonstrate greater values of cardiac mass and volume (the "athlete's heart"). However, studies addressing this issue have frequently failed to match training volumes between groups or provided inadequate adjustment of variables for body size and composition. This study compared echocardiographic anatomic features in 8 female and 8 male competitive cyclists with a similar training history. Conforming to most previous reports, left ventricular mass and end diastolic dimension, adjusted for fat free body mass and body surface area, respectively, were greater in the males (3.56 ± 0.83 g kg-1 versus 2.50 ± 0.38 g kg-1; 41.7 ± 2.2 mm and 37.4 ± 2.5 mm per BSA0.5). This study indicated that when training volume as well as body size and composition are considered, male endurance athletes exhibit greater cardiac dimensions and mass compared to their female counterparts.